Does Say-on-Pay (SoP) Affect CEO Compensation Following an M&A Deal? - Chen, Shuyang (Université d'Ottawa / University of Ottawa, 2018)
This study examines the effectiveness of Say on Pay (SoP) regulation as a corporate governance mechanism in the context of M&A deals. Using a large sample of U.S. firms over the 2005-2017 period, this study finds that, in the post-SoP period, overall CEO pay growth rate declines and CEO pay to acquisition performance sensitivity improves following M&A activities. This supports ‘SoP governance’ hypothesis, which proposes that SoP regulation will restrict CEOs self-fulfilling behaviour. In a macro-economic set-up, the introduction of SoP regulation was intended to discipline top managers by giving shareholders an opportunity to express their opinion on CEO compensation. It was therefore expected that, in the post SoP-era, CEOs will experience a lower growth in their pay package following M&A deals. On the other hand, the relation between SOP voting approval rates and CEO compensation following M&A activities is unidirectional. Irrespective of the performance of M&A deals, it is observed that CEOs with higher shareholder voting approval experience a significant positive change in their compensation level after an M&A deal. We term this as a ‘reliable CEO’ hypothesis. According to the ‘reliable CEO hypothesis, a very high voting percentage may legitimize CEOs action and embolden CEOs to carry out more risky ventures such as M&As. Since there is an established relation between risk and return, shareholders would like CEOs to take appropriate risks to increase firm value. A reliable CEO, who enjoys a high degree of shareholders’ support, should not be penalized for taking more risky ventures that are intended to increase shareholders’ wealth. Our results confirm this viewpoint.
Keywords: Say-on-Pay; CEO Compensation; M&A Deal